Health Education; The Comparison Between With Leaflet and Video Using Local Language In Improving Teenager’s Knowledge of Adverse Health Effect of Smoking - Abdullah Abdullah; Andan Firmansyah; Asri Aprilia Rohman; Nurisriani Najamuddin; Rahmayanti Puang Kuma (Universitas Faletehan, 2020)
Smoking is a usual activity that we always find in our society, although most of the people know the danger of it, the habit of smoking still can be found in a big amount in our society, especially in the teenage area, whose stand in the biggest amount of smoker in Indonesia in this present. Health education changes attitude of young generation through knowledge, which is influence by several elements, such as delivered information, manner or props used, and language. The purpose of this research was to identify the comparison of leaflets and videos using local language to improve knowledge of the adverse health effects of smoking in the teenager. This research used the Quasi Experiment design with Pretest and Posttest Two Group of 120 respondents. The questionnaire used to examine the knowledge of respondents. The result using the Wilcoxon test showed that leaflet and video with local language are equally effective to increase knowledge of respondents of the health effects of smoking(p= -0.000), mean score after intervention by using the local language leaflet is 1.98, and mean score by using local language video is 2.32. So, local video is more effective to improve the knowledge of teenagers about the danger of smoking than the use of local language leaflets.